Interference with the bromodomain epigenome readers drives p21 expression and tumor senescence. (1st October 2019) - Webber, Liana P.; Yujra, Veronica Q.; Vargas, Pablo A.; Martins, Manoela D.; Squarize, Cristiane H.; Castilho, Rogerio M.
Abstract: Head and neck cancer (HNSCC) are one of the most common solid malignancies of the world, being responsible for over 350, 000 deaths every year. Much of the complications in managing and treating HNSCC advent from the complex genetic and epigenetic landscape of the disease. Emerging information has shown promising results in targeting BRD4, an epigenetic regulator bromodomain that functions as a scaffold for transcription factors at promoters and super-enhancers. Here we show that by disrupting the interaction between BRD4 and histones using the bromodomain inhibitor JQ1, HNSCC cells undergo cell growth arrest followed by cellular senescence. Mechanistically, JQ1 negatively impacted the phosphorylation levels of SIRT1 along with the acetylation levels of mutant p53 (active). In vivo administration of JQ1 resulted in disruption of HNSCC growth along with the activation of cellular senescence, observed by the accumulation of DNA double-strand breaks, p16 ink4, accumulation of senescence-associated beta-galactosidase, and loss of phosphorylated Sirt1 ser47 . Furthermore, we also demonstrate that JQ1 was efficient in reducing the population of cancer stem cells from HNSCC xenografts. Highlights: Disruption of the BRD4-Histone interaction results in tumor growth arrest. Bet inhibitor activates cellular senescence in HNSCC cell lines and xenograft tumors with wildtype CDKN2A. In vivo administration of JQ1 negatively impacts the population of stem cell-like cancer cells.